An experimental estimate of the impact produced on PNU by new generation video codecs. (5th May 2020) - Bruno, Andrea; Cattaneo, Giuseppe
The resolution of video cameras has increased considerably in recent years leading to a new generation of codecs with higher compression rates, such as H.265, VP9 and AV1. However, compression can heavily affect the noise present in each frame. Other encoder specific features, like the intra-frame prediction for H.265 and AV1, can flatten the pixel non-uniformity (PNU) noise. We implemented a test-bed to establish whether source camera identification can still be achieved using the PNU when videos are encoded in those formats. The experiments proved that the results are less accurate than those obtained from videos encoded with traditional codecs. Nevertheless, the most original result achieved was the methodology we designed. In order to avoid hidden artifacts the source videos were initially acquired as a raw data stream from a dedicated embedded system and then recorded with an open-source YUV encoder.